Endometrioid Adenocarcinoma Metastatic to the Thyroid, Presenting Like Anaplastic Thyroid Cancer - Natasha Pollak; Gregory J. Renner; Ronald Miick; Shellaine R. Frazier (Case Reports in Endocrinology)
Metastasis of uterine cancer to the head and neck is extremely rare. We report what we believe to be the first documented case of endometrioid adenocarcinoma metastasizing to the thyroid gland. An 80-year-old woman was referred to the otolaryngology service with a rapidly growing neck mass. The mass appeared to originate from the thyroid gland. Her clinical presentation was consistent with anaplastic thyroid carcinoma. A tracheostomy was performed. An open biopsy established the diagnosis of moderately differentiated adenocarcinoma, consistent with a gynecologic primary. The patient had undergone a hysterectomy 5 years prior for endometrioid adenocarcinoma. The thyroid tumor histology and immunophenotype corresponded well with her prior endometrial carcinoma, indicating that the thyroid mass was a metastasis from the endometrial primary. Radiotherapy appears to offer good local disease control in this rare case of endometrioid adenocarcinoma metastatic to the thyroid.